2010
DOI: 10.1136/bmj.c654
|View full text |Cite|
|
Sign up to set email alerts
|

Educational inequalities in mortality over four decades in Norway: prospective study of middle aged men and women followed for cause specific mortality, 1960-2000

Abstract: Objectives To determine the extent to which educational inequalities in relation to mortality widened in Norway during 1960-2000 and which causes of death were the main drivers of this disparity.Design Nationally representative prospective study.Setting Four cohorts of the Norwegian population aged 45-64 years in 1960, 1970, 1980, and 1990 and followed up for mortality over 10 years.Participants 359 547 deaths and 32 904 589 person years.Main outcome measures All cause mortality and deaths due to cancer of lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 22 publications
9
95
0
6
Order By: Relevance
“…In previous studies, increasing mortality inequalities are shown to be driven by an increasing gap in cardiovascular disease mortality (Mackenbach et al, 2003) and other smoking-related causes of death such as lung cancer and lower respiratory diseases (Strand et al, 2010). In Finland, the increase is mainly explained by a growing disparity in alcohol-related deaths, as well as many cancers, between high-and low-income groups (Tarkiainen, Martikainen, Laaksonen, and Valkonen, 2012).…”
Section: Related Literaturementioning
confidence: 96%
See 1 more Smart Citation
“…In previous studies, increasing mortality inequalities are shown to be driven by an increasing gap in cardiovascular disease mortality (Mackenbach et al, 2003) and other smoking-related causes of death such as lung cancer and lower respiratory diseases (Strand et al, 2010). In Finland, the increase is mainly explained by a growing disparity in alcohol-related deaths, as well as many cancers, between high-and low-income groups (Tarkiainen, Martikainen, Laaksonen, and Valkonen, 2012).…”
Section: Related Literaturementioning
confidence: 96%
“…Increasing differences in life expectancy between socio-economic groups have recently been observed in a number of high-income countries; for example in the US (Montez and Zajacova, 2013); the UK (Marmot and Brunner, 2005), and in Norway (Steingrimsdottir et al, 2012;Strand et al, 2010). For Sweden, the difference in mortality risk between educational levels has widened during the last decades (Shkolnikov et al, 2012; The National Board of Health and Welfare [Socialstyrelsen], 2013).…”
Section: Related Literaturementioning
confidence: 99%
“…Causespecific mortality rates might provide some clues. In middle aged populations, and especially among men, cardiovascular mortality has been the main cause of increasing socio-economic-based inequalities in mortality [46,47]. A frequently suggested explanation has been the tobacco epidemic [45,48,49].…”
Section: Explanation and Interpretation Of Our Resultsmentioning
confidence: 99%
“…Such data sources have been used to investigate the effect of education on lifetime outcomes, including analyzing the effects of schooling on morbidity and lifespans. Some of the largest available studies, including those with full population coverage and a relatively broad set of control variables, suggest a strong positive association of education with longevity (Strand et al 2010;Remes et al 2010;Brønnum-Hansen et al 2004). …”
Section: Effects Of Education On Health and Mortalitymentioning
confidence: 99%